2014
DOI: 10.1634/theoncologist.2014-0234
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Alterations in ERBB2/HER2 Represent Potential Therapeutic Targets Across Tumors From Diverse Anatomic Sites of Origin

Abstract: Background. Targeted ERBB2/HER2 inhibitors are approved by the U.S. Food and Drug Administration for the treatment of breast, gastric, and esophageal cancers that overexpress or amplify HER2/ERBB2, as measured by immunohistochemistry (IHC) and fluorescence in situ hybridization (FISH), respectively. Activating mutations in ERBB2 have also been reported and are predicted to confer sensitivity to these targeted agents.Testing for these mutations is not performed routinely, and FISH and IHC are not applied outsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 49 publications
2
65
0
Order By: Relevance
“…Genomic profiling of human cancers has identified recurrent somatic mutations of HER2 ( ERBB2 ) and HER3 ( ERBB3 ), typically occurring in the absence of gene amplification 13 . Mutations in HER2 are clustered in the extracellular, transmembrane, and kinase domains.…”
Section: Introductionmentioning
confidence: 99%
“…Genomic profiling of human cancers has identified recurrent somatic mutations of HER2 ( ERBB2 ) and HER3 ( ERBB3 ), typically occurring in the absence of gene amplification 13 . Mutations in HER2 are clustered in the extracellular, transmembrane, and kinase domains.…”
Section: Introductionmentioning
confidence: 99%
“…Recent publications have suggested a broad spectrum of genomic changes in clinically relevant targets (29,(36)(37)(38), and expanded analyses are warranted to identify more patients predicted to be sensitive or resistant to targeted therapies. Furthermore, the identification of drug sensitivity and resistance biomarkers across multiple indications suggests that targeted agents may have broader utility beyond that for which they were approved originally.…”
Section: Spectrum Of Known Clinically Relevant Alterations Across Dismentioning
confidence: 99%
“…DNA sequencing efforts have revealed that ERBB2 , the gene encoding the HER2 receptor tyrosine kinase (RTK), is mutated a wide variety of cancer types, including 2–3% of primary breast cancers (13), with a higher incidence in lobular breast cancers (4). More than 70% of HER2 mutations in breast cancer are found in the absence of HER2 ( ERBB2 ) gene amplification (2).…”
Section: Introductionmentioning
confidence: 99%